Grana-Localized Proteins, RIQ1 and RIQ2, Affect the Organization of Light-Harvesting Complex II and Grana Stacking in Arabidopsis. Issue 9 (6th September 2016) - Yokoyama, Ryo; Yamamoto, Hiroshi; Kondo, Maki; Takeda, Satomi; Ifuku, Kentaro; Fukao, Yoichiro; Kamei, Yasuhiro; Nishimura, Mikio; Shikanai, Toshiharu
Abstract : The Arabidopsis riq1 and riq2 mutants have enhanced grana stacking and were defective in NPQ induction and state transitions, demonstrating a link between LHCII organization and thylakoid structure. Abstract: Grana are stacked thylakoid membrane structures in land plants that contain PSII and light-harvesting complex II proteins (LHCIIs). We isolated two Arabidopsis thaliana mutants, reduced induction of non-photochemical quenching1 ( riq1 ) and riq2, in which stacking of grana was enhanced. The curvature thylakoid 1a ( curt1a ) mutant was previously shown to lack grana structure. In riq1 curt1a, the grana were enlarged with more stacking, and in riq2 curt1a, the thylakoids were abnormally stacked and aggregated. Despite having different phenotypes in thylakoid structure, riq1, riq2, and curt1a showed a similar defect in the level of nonphotochemical quenching of chlorophyll fluorescence (NPQ). In riq curt1a double mutants, NPQ induction was more severely affected than in either single mutant. In riq mutants, state transitions were inhibited and the PSII antennae were smaller than in wild-type plants. The riq defects did not affect NPQ induction in the chlorophyll b -less mutant. RIQ1 and RIQ2 are paralogous and encode uncharacterized grana thylakoid proteins, but despite the high level of identity of the sequence, the functions of RIQ1 and RIQ2 were not redundant. RIQ1 is required for RIQ2 accumulation, and the wild-type level of RIQ2 did not complement the NPQ and thylakoid phenotypes in riq1 . We propose that RIQ proteins link the grana structure and organization of LHCIIs.